2020
DOI: 10.3390/jcm9072316
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Extent of Surgery on the Long-Term Outcomes of Patients with Low-Risk Differentiated Non-Medullary Thyroid Cancer: A Systematic Meta-Analysis

Abstract: Recently, the management of patients with low-risk differentiated non-medullary thyroid cancer (DTC), including papillary and follicular thyroid carcinoma subtypes, has been critically appraised, questioning whether these patients might be overtreated without a clear clinical benefit. The American Thyroid Association (ATA) guideline suggests that thyroid lobectomy (TL) could be a safe alternative for total thyroidectomy (TT) in patients with DTC up to 4 cm limited to the thyroid, without metastases. We conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…The most common complications of thyroidectomy include recurrent laryngeal nerve injury, hypoparathyroidism, hematoma, and wound infection . Recently, there has been increased controversy regarding the optimal management of DTC . The issue is complications related to TT vs cancer residue and recurrence risks related to TL, both of which are associated with the HRQOL of patients with DTC.…”
Section: Introductionmentioning
confidence: 99%
“…The most common complications of thyroidectomy include recurrent laryngeal nerve injury, hypoparathyroidism, hematoma, and wound infection . Recently, there has been increased controversy regarding the optimal management of DTC . The issue is complications related to TT vs cancer residue and recurrence risks related to TL, both of which are associated with the HRQOL of patients with DTC.…”
Section: Introductionmentioning
confidence: 99%
“…The median recurrence rate was the same in TL and TT groups -7%. Similarly, OS in both groups was 93% [28].…”
Section: Fig 1 the Difference Between Lobectomy And Loboisthmectomymentioning
confidence: 81%
“…Taking into account that the tumors treated only with lobectomy do indeed meet the histopathological criteria for lobectomy-1 to 4 cm, unifocal, without microscopic extrathyroidal extension or microscopic lymph node metastases-cancer recurrence rates in the range of 2.7-11.8% have been reported. In a recent meta-analysis of 175,430 patients, Bojoga et al reported a 7% rate of cancer recurrence [58]. This large meta-analysis found no difference in recurrence rates for intrathyroidal cancers up to 4 cm in diameter without lymph node metastases, treated with lobectomy or with total thyroidectomy.…”
Section: Oncologic Considerations: Recurrence In the Contralateral Lomentioning
confidence: 97%